Proximate Composition, Mineral Content and Fatty Acids Analyses of Aromatic and Non-Aromatic Indian Rice - Verma, Deepak Kumar; Srivastav, Prem Prakash (Rice science, 2017)
Awareness on nutritive value and health benefits of rice is of vital importance in order to increase the consumption of rice in daily diet of the human beings. In this study, a total of six aromatic and two non-aromatic rice accessions grown in India were analysed for their nutritional quality attributes including proximate composition, mineral contents and fatty acids. Data with three replications were used to measure Pearson＇s simple correlation co-efficient in order to establish the relationship among various nutritional quality attributes. The result on proximate composition showed that Govind Bhog had the highest moisture（13.57%） and fat（0.92%） content, which signifies its tasty attribute. Badshah Bhog exhibited the highest fibre content（0.85%）, carbohydrate content（82.70%） and food energy（365.23 k Cal per 100 g）. Among the minerals, the higher Ca（98.75 mg/kg）, Zn（17.00 mg/kg） and Fe（31.50 mg/kg） were in Gopal Bhog, whereas the highest Na（68.85 mg/kg） was in Badshah Bhog, the highest K（500.00 mg/kg） was in Swetganga, Khushboo and Sarbati. The highest contents of unsaturated fatty acids viz. oleic acid（49.14%）, linoleic acid（46.99%） and linolenic acid（1.27%） were found in Sarbati, whereas the highest content of saturated fatty acids viz. myristic acid（4.60%） and palmitic acid（31.91%） were found in Govind Bhog and stearic acid（6.47%） in Todal. The identified aromatic rice accessions Gopal Bhog, Govind Bhog and Badshah Bhog and non-aromatic rice accession Sarbati were found nutritionally superior among all eight tested accessions. The nutritional quality oriented attributes in this study were competent with recognized prominent aromatic and non-aromatic rice accessions as an index of their nutritional worth and recommend to farmers and consumers which may be graded as export quality rice with good unique nutritional values in international market.